Magnitude and associated factors of benign prostatic hyperplasia among male patients admitted at surgical ward of selected governmental hospitals in Sidamma region, Ethiopia 2021 - Bereket Beyene Gebre; Melese Gebrie; Mubarek Bedru; Vallen Bennat (Elsevier, 2024)
Background: Benign prostatic hyperplasia (BPH) is the most common cause of bladder outlet obstruction and voiding symptoms in elderly men, and it affects more than 50 % of men over 60 years of age globally. Methods: Between October 15 and November 15, 2021, 143 male patients admitted to the surgical wards of the Hawassa University Comprehensive Specialized Hospital (HUCSH), the Adare General Hospital (AGH), and the Yirgalem General Hospital in Hawassa City were involved. Data were gathered utilizing a pretested, structured, interviewer-administered questionnaire and patient review checklist employing a purposive sample technique. A binary logistic regression model, which examines the relationship between the dependent and independent variables, was used to analyze the data using SPSS version 20. Results: The magnitude of benign prostate hyperplasia (BPH) was 27 (18.9 %). Old age >=75 years (AOR = 0.07; 95 % CI: 0.005-1.024), being smokers (AOR = 0.261; 95 % CI: 0.078-00.871), positive familial history of BPH (AOR = 0.13; 95 % CI: 0.038-00.428), patients with renal disease (AOR = 5.724; 95 % CI: 1.669-19.631), and patients with a history of difficulties with sexual activity (AOR = 0.17; 95 % CI: 0.034-00.830) were found to be statistically associated with the presence of BPH. Conclusions: In conclusion, the findings of this study revealed that BPH was a prevalent disease among men. Factors that could potentially increase the risk of benign prostatic hyperplasia were old age, positive family history, smoking, renal disease, and difficulties with sexual activities.